Impactos do setor de biocombustíveis: aspectos socioeconômicos e da expansão territorial urbana no município de Lins, SP - Montanha, Enaldo Pires (Universidade Federal de São Carlos, 2012)
This study represents a theoretical and empirical research on the possible interferences of the productive sector of biofuels on the towns and small producers on the surrounding area of operation of the industries. Objective: analyze the socioeconomic dynamics and form of expansion of urban land in the city of Lins, in the period 2000 to 2010, correlated with the growth of the biofuels sector in its surroundings. Method: survey data on the region of Lins and 13 municipalities in the Escritório de Desenvolvimento Rural de Lins (EDR-Lins), during the ten years delimited. Preparation of use and expansion of land by georreferenced mapping built with the assistance of imagens originated by Landsat 5 sensor TM, bands 3, 4 e 5, scene 221/75, collected between 2000 and 2010, provided by the Image Catalog belonging to Instituto Nacional de Pesquisas Espaciais (INPE), confronted with images produced by SPRING 5.1.18 (property of INPE) and SIG CTGEO (property of Centro de Tecnologia em Geoprocessamento CTGEO) software. Statistical correlation of regional development indicators taken from the Índice Firjan de Desenvolvimento Municipal (IFDM) and production of raw material extracted from the data of the Instituto Econômico Agrícola de São Paulo (IEA) of the EDR-Lins. Results: Contrary to expectation, the results failed to indicate a significant correlation between the implementation and performance of biofuel and/or biodiesel factories and municipal development, whether in relation to territorial expansion, whether in relation to socioeconomic variability. Wages paid to workers in the sugarcane sector, day laborer and monthly employee, and administrators were about 280% to 300% below the increase in production, which shows a possible concentration of income in executive and owners of power plants. In the delimited period, while there was an increase of 130% of the production of cane sugar, there was an increase of only 20% of the IFDM. When considering the specific indicators of the evolution of the population with the specific indicators of the evolution of production of cane sugar has obtained a moderate correlation, but that can t be attributed solely to the expansion of biofuel in the region. Conclusion: growth of the biofuels sector in the municipality of Lins did not produce whole supposed positive effects expected on the pattern and organization of the life of the resident population; neither added a significant improvement in municipal rates of the cities that integrate the EDR-Lins, such as income and population employed. Overall, the results show that the Law 11.097/2005 hasn t achieved one of its main goals, which is the promotion of quality of life of small producers dedicated to the cultivation of oil plants.
Impacts of the biofuels sector: socioeconomics and land urban expansion aspects in the city of Lins, SP
Keywords: Planejamento urbano; Energia da biomassa; Biodiesel; Desenvolvimento regional; Cana-de-açúcar; Desenvolvimento municipal; Lei 11.097/2007; Biofuel; Biodiesel; Municipal development; Sugarcane; Law 11.097/2007; ENGENHARIAS::ENGENHARIA CIVIL